PENERAPAN LOGIKA FUZZY DALAM SISTEM PRAKIRAAN CUACA BERBASIS MIKROKONTROLER - , Tedy Rismawan, Velma Kurniati , Dedi Triyanto (Coding Jurnal Komputer dan Aplikasi, 2017)
Weather is one of the important factors in supporting human activities. The difference of weather between another place caused by the changes of air temperature, humidity and air pressure. Parameters that are considered for predicting weather are air temperature, humidity and air pressure. Fuzzy logic using Sugeno method acts as a significant function in decision making procedure. Fuzzy logic using Sugeno method is best used in forecasting because it has a tolerance to incorrect data and contains uncertainty that can be applied to weather forecasting systems. This research uses Arduino Uno microcontroller. The output from this research is the information on the value of air temperature, air humidity, air pressure and the prediction of weather. The 3 (three) results of weather forecasts generated in this study is the weather conditions such as rain, cloudy or bright. The success of the system based on the comparison between the system and the actual weather is 74%.Keywords: Weather, Fuzzy Logic, Method, Arduino